2010
DOI: 10.5010/jpb.2010.37.1.072
|View full text |Cite
|
Sign up to set email alerts
|

Development of transgenic cucumber expressing TPSP gene and morphological alterations

Abstract: To develop transgenic cucumber tolerant to abiotic stress, a cotyledonary-node explants were co-cultivated with Agrobacterium tumefaciens (EHA101) carrying TPSP gene (pHC30-TPSP). After transfer to fresh medium every two week for eight weeks, putative transgenic plants were selected when shoots grown a length greater than 3 cm from the cotyledonary-node explants on selection medium supplemented with 5 mgl -1 phospinotricin as selectable agent. The confirmation of transgenic cucumber was based on the Northern b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Cotyledonary node explants showed a very high regeneration frequency (94.3%) when incubated on MS medium supplementing with 6.66 μmol L -1 BA, and its transformation rate was approximately 4.8% (Wang et al 2013). However, the transformation efficiency of cotyledonary node explants was only 1.7% in another study (Kim et al 2010). Wang et al (2014) found the ratio of the transformation rate between cucumber cotyledon and hypocotyl explants was 2-fold.…”
Section: Agrobacterium-mediated Transformationmentioning
confidence: 92%
See 4 more Smart Citations
“…Cotyledonary node explants showed a very high regeneration frequency (94.3%) when incubated on MS medium supplementing with 6.66 μmol L -1 BA, and its transformation rate was approximately 4.8% (Wang et al 2013). However, the transformation efficiency of cotyledonary node explants was only 1.7% in another study (Kim et al 2010). Wang et al (2014) found the ratio of the transformation rate between cucumber cotyledon and hypocotyl explants was 2-fold.…”
Section: Agrobacterium-mediated Transformationmentioning
confidence: 92%
“…In fact, Journal of Integrative Agriculture Advance Online Publication 2014 doi: 10.1016/S2095-3119(14)60899-6 target genes were introduced into cucumber genome mostly by Agrobacterium -mediated transformation approach. In the procedure of Agrobacterium-mediated transformation, the transformation frequency is depended on several main factors including plant regeneration frequency, plant genotype, Agrobacterium strains, bacterial concentration, length of exposure time to Agrobacterium, co-cultivation period, and selection system (Kose and Koç 2003;Yin et al 2005;Kim et al 2010).…”
Section: Genetic Transformation Methods Used In Cucumbermentioning
confidence: 99%
See 3 more Smart Citations